2017
DOI: 10.1111/jphp.12844
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potency of pharmacological adenosine receptor agonist/antagonist in angiogenesis, current status and perspectives

Abstract: Objectives Adenosine concentration significantly increases in tumour microenvironment contributing to tumorigenic processes including cell proliferation, survival, invasion and of special interest in this review angiogenesis. Key findings This review summarizes the role of pharmacological adenosine receptor agonist and antagonist in regulating angiogenesis for a better understanding and hence a better management of angiogenesis-associated disorders. Summary Depending upon the pharmacological characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
(87 reference statements)
1
12
0
Order By: Relevance
“…By additional investigation of the A2a AR role in angiogenesis, Liu et al (2010) demonstrated that inactivation of A2a AR attenuates retinopathy angiogenesis which is oxygen-induced only. Normal retinal vascularization not involved, supporting the therapeutic potency of A2a AR antagonists for retinopathy (Sun et al, 2011;Bahreyni et al, 2018). This angiogenic ability of adenosine could explain the results of the present study manifested by increased vascularity, congestion of blood vessels and hemorrhage.…”
Section: Resultssupporting
confidence: 80%
“…By additional investigation of the A2a AR role in angiogenesis, Liu et al (2010) demonstrated that inactivation of A2a AR attenuates retinopathy angiogenesis which is oxygen-induced only. Normal retinal vascularization not involved, supporting the therapeutic potency of A2a AR antagonists for retinopathy (Sun et al, 2011;Bahreyni et al, 2018). This angiogenic ability of adenosine could explain the results of the present study manifested by increased vascularity, congestion of blood vessels and hemorrhage.…”
Section: Resultssupporting
confidence: 80%
“…A 1 and A 2B receptors upregulate IL‐8, while A 2A receptors stimulate IL‐10 release. VEGF levels are increased by A 2A , A 2B , and A 3 receptor activities; HIF‐1α is elevated in response to A 3 receptor stimulation, and iNOS/endothelial NO synthase (eNOS) expression levels are upregulated, respectively, as consequence of A 2A and A 2B receptor activities (161). Interactions between murine A 2A and TLR‐2, ‐4, ‐7, and ‐9 in macrophages have been reported, upregulating VEGF and downregulating TNF‐α generating a so‐called angiogenic switch (162).…”
Section: Macrophages and Cancer Biologymentioning
confidence: 99%
“…48,49 However, in some tumor cell lines, A1AR agonists inhibit tumor cell proliferation, 50,51 whereas in others, adenosine-induced A1 activation elicits a proapoptotic response by activation of caspases 3, 8, and 9. 35 The role of ARs has been investigated in various cancers [52][53][54] (Figure 1). Jafari et al 42 demonstrated that activation of A3AR by Cl-IB-MECA, an A3AR agonist, suppresses breast cancer stem cell proliferation by inhibition of extracellular signal-regulated kinases 1/2 (ERK1/2) and glioma-associated oncogene (GLI-1) pathways leading to cell cycle arrest and apoptosis in these cells.…”
Section: Adenosine Signaling In Cancer Pathologymentioning
confidence: 99%
“…The role of ARs has been investigated in various cancers (Figure ). Jafari et al demonstrated that activation of A3AR by Cl‐IB‐MECA, an A3AR agonist, suppresses breast cancer stem cell proliferation by inhibition of extracellular signal‐regulated kinases 1/2 (ERK1/2) and glioma‐associated oncogene (GLI‐1) pathways leading to cell cycle arrest and apoptosis in these cells.…”
Section: Adenosine Signaling In Cancer Pathologymentioning
confidence: 99%